Alumni network, CEO turnover, and stock price crash risk: evidence from China - Jing Liu (Cogent Economics & Finance, 2022)
This paper empirically tests the impact of CEO's alumni relationships on the stock price crash risk during CEO turnover. Empirical tests find that CEOs' advantage among alumni networks will increase stock price crash risk during CEO turnover to some degree. However, this effect is built on the CEO's power inside the firm that was established during the long tenure on the position. Further research finds that analysts' following can exacerbate the release of bad news, however, it seems that the either internal corporate governance or external cannot effectively monitor the opportunistic behavior of CEOs on the whole. In addition, the positive effect of alumni network on stock price crash risk mainly exists in the regions where the legal environment is weak, that is, a sound legal environment can effectively prevent the opportunistic behavior of managers. Besides, the experience of the M.B.A program may strengthen the CEO's tendency to take advantage of alumni connections to withhold bad news. This paper sheds light on the risk that social connection may bring and conducts to a more comprehensive understanding of the role that social network plays in business activities.
Keywords: G14; G34; 330; Social networks; CEO tenure; stock price crash risk; Tenure; CEO successor